I spy treasure hunt : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Cartwheel Books, 1999)
Rhyming verses ask readers to find hidden objects in the photographs.
Keywords: Picture puzzles -- Juvenile literature; Riddles -- Juvenile literature; Puzzles -- Juvenile literature